Global attentional-executive sequelae following surgical lesions to globus pallidus interna - Scott, R; Harrison, J; Boulton, C; Wilson, J; Gregory, R; Parkin, S; Bain, P; Joint, C; Stein, J; Aziz, T (2002)
It has been demonstrated that selective unilateral surgical ablation of posteroventral globus pallidus interna relieves the movement disorders associated with advanced Parkinson's disease, without necessarily incurring the executive cognitive sequelae that have been observed following gross pathological lesions to this brain region. This finding is consistent with established theory that underlying neuronal circuitry is functionally segregated into parallel cortico-striatal-pallidal-thalamocortical 'loops'. We have studied a series of 12 patients with advanced Parkinson's disease at baseline, and then following bilateral pallidotomy, with a battery of neuropsychological tests including the Cambridge Neuropsychological Test Automated Battery. We identified a selective and universal loss of individual patients' ability to shift attention to novel dimensions in a test of abstract rule-learning following surgery, which was not reliably associated with any other change in cognition, personality, mood or medication. This finding is rare in its specificity and has implications for theoretical models of the functional architecture and pathophysiology of the globus pallidus, and the clinical practice of pallidotomy.